Identifying and reducing errors with surgical simulation. (1st October 2004) - Fried, M P; Satava, R; Weghorst, S; Gallagher, A G; Sasaki, C; Ross, D; Sinanan, M; Uribe, J I; Zeltsan, M; Arora, H; Cuellar, H
Abstract : The major determinant of a patient's safety and outcome is the skill and judgment of the surgeon. While knowledge base and decision processing are evaluated during residency, technical skills—which are at the core of the profession—are not evaluated. Innovative state of the art simulation devices that train both surgical tasks and skills, without risk to patients, should allow for the detection and analysis of errors and "near misses". Studies have validated the use of a sophisticated endoscopic sinus surgery simulator (ES3) for training residents on a procedural basis. Assessments are proceeding as to whether the integration of a comprehensive ES3 training programme into the residency curriculum will have long term effects on surgical performance and patient outcomes. Using various otolaryngology residencies, subjects are exposed to mentored training on the ES3 as well as to minimally invasive trainers such as the MIST-VR. Technical errors are identified and quantified on the simulator and intraoperatively. Through a web based database, individual performance can be compared against a national standard. An upgraded version of the ES3 will be developed which will support patient specific anatomical models. This advance will allow study of the effects of simulated rehearsal of patient specific procedures (mission rehearsal) on patient outcomes and surgical errors during the actual procedure. The information gained from these studies will help usher in the next generation of surgical simulators that are anticipated to have significant impact on patient safety.